Marketing in healthcare-related industries - Hinson, Robert; Adeola, Ogechi; Limbu, Yam B.; Mogaji, Emmanuel (Emerald Publishing Limited : Information Age Publishing, Inc., 2020)
"Healthcare delivery and the healthcare industry in the 21st century face a multiplicity of challenges. These include changing disease patterns, more technology-driven health interventions, a more assertive and quality conscious clientele, as well as a rapidly growing for-profit segment of the industry. This places more responsibilities on healthcare service providers in both the public and private sectors to deliver value-for-money services at competitive costs. To respond to this, a carefully crafted marketing approach is needed by all players in the industry to sustain the confidence of its clientele. Marketing in Healthcare-Related Industries captures the concepts and complexities of marketing healthcare in today's environment. The book provides detailed conceptual and practical insights that will be of great benefit to healthcare students and practitioners. Topics on healthcare marketing have been carefully selected to provide wide coverage and are illustrated by mini-cases with a highly practical marketing tool kit for healthcare managers also included"-- Provided by publisher.
Keywords: Medical care -- Marketing.; Business & Economics -- Industries -- Healthcare.; Health economics.; Industry and industrial studies.; Health systems and services.; elektronické knihy; electronic books